2013
DOI: 10.1089/apc.2013.0015
|View full text |Cite
|
Sign up to set email alerts
|

Insights on GRACE (Gender, Race, And Clinical Experience) from the Patient's Perspective: GRACE Participant Survey

Abstract: The Gender, Race And Clinical Experience (GRACE) study was conducted between October 2006 and December 2008 to evaluate sex-and race-based differences in outcomes after treatment with a darunavir/ritonavir-based antiretroviral regimen. Between June 2010 and June 2011, former participants of the GRACE trial at participating sites were asked to complete a 40-item questionnaire as part of the GRACE Participant Survey study, with a primary objective of assessing patients' characteristics, experiences, and opinions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Our results are similar to those of some clinical trials when they found a higher frequency of virological failure in women, factors associated with non-adherence, antiretroviral discontinuation, and poor virologic response in univariate analyses were being the primary caregiver for children, unemployment, and transportation difficulties, respectively, and the major sex-based differences in response may be due to higher discontinuation rates in women [17,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are similar to those of some clinical trials when they found a higher frequency of virological failure in women, factors associated with non-adherence, antiretroviral discontinuation, and poor virologic response in univariate analyses were being the primary caregiver for children, unemployment, and transportation difficulties, respectively, and the major sex-based differences in response may be due to higher discontinuation rates in women [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…In Mexico, studies conducted in the north of the country in 2006 by Peñarrieta et al and Piña-López et al reported different rates of adherence (50-52%). These used the adherence questionnaire VPAD24 [12,17]. In our study, we decided to use the SMAQ questionnaire because it is easier to use, with a sensitivity of 72% and specificity of 91% [13].…”
Section: Discussionmentioning
confidence: 99%
“…These findings correspond with results from the Gender, Race and Clinical Experience (GRACE) trial that found lower adherence and virologic response among PLHIV who were female and the primary caregivers of children (41). HIV care and support services do not typically address competing childcare, or any caregiving needs and responsibilities of PLHIV or their caregivers, though they may impede health behaviors and affect poor health outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…The study also found that a woman's age at the time she was pregnant was an important predictor of compliance to ART, with younger women experiencing virological failure more frequently [15]. The Gender, Race and Clinical Experience (GRACE) study found that being the primary caregiver for children was associated with poorer compliance with ART [16].…”
Section: Discussionmentioning
confidence: 92%